Cu-Based Materials for Enhanced C2+ Product Selectivity in Photo-/Electro-Catalytic CO2 Reduction: Challenges and Prospects - Rhimi, Baker; Zhou, Min; Yan, Zaoxue; Cai, Xiaoyan; Jiang, Zhifeng (Nano-Micro Letters, 2024)
Carbon dioxide conversion into valuable products using photocatalysis and electrocatalysis is an effective approach to mitigate global environmental issues and the energy shortages. Among the materials utilized for catalytic reduction of CO2, Cu-based materials are highly advantageous owing to their widespread availability, cost-effectiveness, and environmental sustainability. Furthermore, Cu-based materials demonstrate interesting abilities in the adsorption and activation of carbon dioxide, allowing the formation of C2+ compounds through C–C coupling process. Herein, the basic principles of photocatalytic CO2 reduction reactions (PCO2RR) and electrocatalytic CO2 reduction reaction (ECO2RR) and the pathways for the generation C2+ products are introduced. This review categorizes Cu-based materials into different groups including Cu metal, Cu oxides, Cu alloys, and Cu SACs, Cu heterojunctions based on their catalytic applications. The relationship between the Cu surfaces and their efficiency in both PCO2RR and ECO2RR is emphasized. Through a review of recent studies on PCO2RR and ECO2RR using Cu-based catalysts, the focus is on understanding the underlying reasons for the enhanced selectivity toward C2+ products. Finally, the opportunities and challenges associated with Cu-based materials in the CO2 catalytic reduction applications are presented, along with research directions that can guide for the design of highly active and selective Cu-based materials for CO2 reduction processes in the future. Highlights: 1 The latest advancements in Cu-based catalysts for photocatalytic and electrocatalytic CO2 reduction into C2+ products are reported. 2 The relationship between the Cu surfaces and their efficiency in photocatalytic and electrocatalytic CO2 reduction is emphasized. 3 The opportunities and challenges associated with Cu-based materials in the CO2 catalytic reduction applications are presented.